Non-coding RNAs: targets for Chinese herbal medicine in treating myocardial fibrosis - Wang, Minghui; Yan, Maocai; Tan, Liqiang; Zhao, Xiaona; Liu, Guoqing; Zhang, Zejin; Zhang, Jing; Gao, Honggang; Qin, Wei (Frontiers in Pharmacology, 2024)
Cardiovascular diseases have become the leading cause of death in urban and rural areas.Myocardial fibrosis is a common pathological manifestation at the adaptive and repair stage of cardiovascular diseases, easily predisposing to cardiac death. Non-coding RNAs (ncRNAs),RNA molecules with no coding potential, can regulate gene expression in the occurrence and development of myocardial fibrosis. Recent studies have suggested that Chinese herbal medicine can relieve myocardial fibrosis through targeting various ncRNAs, mainly including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs).Thus, ncRNAs are novel drug targets for Chinese herbal medicine. Herein, we summarized the current understanding of ncRNAs in the pathogenesis of myocardial fibrosis, and highlighted the contribution of ncRNAs to the therapeutic effect of Chinese herbal medicine on myocardial fibrosis. Further, we discussed the future directions regarding the potential applications of ncRNA-based drug screening platform to screen drugs for myocardial fibrosis.